SARS-CoV-2 N Protein Triggers Acute Lung Injury via Modulating Macrophage Activation and Infiltration in in vitro and in vivo - Lai D; Zhu K; Li S; Xiao Y; Xu Q; Sun Y; Yao P; Ma D; Shu Q (Dove Medical Press, 2023)
Dengming Lai,1,* Kun Zhu,2,* Sisi Li,3,* Yi Xiao,1 Qi Xu,4 Yisheng Sun,5 Pingping Yao,5 Daqing Ma,6,7 Qiang Shu7 1Department of Neonatal Surgery, Children's Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou, People's Republic of China; 2Department of Pathology, The Children's Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou, People's Republic of China; 3School of Medicine, Hangzhou City University, Hangzhou, People's Republic of China; 4School of Laboratory Medicine and Bioengineering, Hangzhou Medical College, Hangzhou, People's Republic of China; 5Key Laboratory of Vaccine, Prevention and Control of Infectious Disease of Zhejiang Province, Zhejiang Provincial Center for Disease Control and Prevention, Hangzhou, People's Republic of China; 6Division of Anaesthetics, Pain Medicine & Intensive Care, Department of Surgery & Cancer, Faculty of Medicine, Imperial College London, Chelsea & Westminster Hospital, London, UK; 7Department of Thoracic and Cardiovascular Surgery, Children's Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiang Shu, Department of Thoracic and Cardiovascular Surgery, Children's Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310052, People's Republic of China, Tel +86-13906500193, Email shuqiang@zju.edu.cn Dengming Lai, Department of Neonatal Surgery, Children's Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, 310052, People's Republic of China, Tel +86-13567164728, Email dengming_lai@zju.edu.cnBackground: SARS-CoV-2-induced acute lung injury but its nucleocapsid (N) and/or Spike (S) protein involvements in the disease pathology remain elusive.Methods: In vitro, the cultured THP-1 macrophages were stimulated with alive SARS-CoV-2 virus at different loading dose, N protein or S protein with/without TICAM2-siRNA, TIRAP-siRNA or MyD88-siRNA. The TICAM2, TIRAP and MyD88 expression in the THP-1 cells after N protein stimulation were determined. In vivo, naïve mice or mice with depletion macrophages were injected with N protein or dead SARS-CoV-2. The macrophages in the lung were analyzed with flow cytometry, and lung sections were stained with H&E or immunohistochemistry. Culture supernatants and serum were harvested for cytokines measurements with cytometric bead array.Results: Alive SARS-CoV-2 virus or N protein but not S protein induced high cytokine releases from macrophages in a time or virus loading dependent manner. MyD88 and TIRAP but not TICAM2 were highly involved in macrophage activation triggered by N protein whilst both inhibited with siRNA decreased inflammatory responses. Moreover, N protein and dead SARS-CoV-2 caused systemic inflammation, macrophage accumulation and acute lung injury in mice. Macrophage depletion in mice decreased cytokines in response to N protein.Conclusion: SARS-CoV-2 and its N protein but not S protein induced acute lung injury and systemic inflammation, which was closely related to macrophage activation, infiltration and release cytokines.Keywords: SARS-CoV-2, S protein, N protein, macrophage, cytokine, acute lung injury